Quintet Educational Cards on Breast Cancer Patients’ Knowledge Regarding Nutrition - Mutia Nadra Maulida; Hikayati; Devin Alfira (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. Nutrition is important in undergoing treatment and healing process in breast cancer patients. The incidence of malnutrition and nutritional disorders in breast cancer patients reaches 35-70% of 72 breast cancer patients. One of the factors that can influence patients' attitudes toward managing nutrition in breast cancer patients is increasing knowledge through health education. This study aims to determine the effect of quintet card educational media on breast cancer patients' level of nutrition knowledge. Methods. This type of research is a quantitative pre-experimental study with a one-group pretest-posttest design. The population in this study was breast cancer patients in the Association for Supporting Women with Breast Cancer (ASWBC). The sample in this study consisted of 27 respondents. Sampling using a purposive sampling method. The statistical analysis used in this study is the marginal homogeneity test. Results. The analysis showed a p-value of 0.000 (α ≤ 0.05), which showed a significant difference in knowledge about nutrition in breast cancer patients before and after health education was carried out through the quintet card educational media. Nutrition knowledge is urgently needed by breast cancer patients and the quintet card educational media can be used as information material about nutrition in breast cancer patients and can be used in activities in the ASWBC. Conclusion. This educational media can be used by breast cancer patients following SOP as a play guide and as a media for health education.